2018
DOI: 10.1111/psyg.12359
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy for older adult patients with major depressive disorder: a systematic review of randomized controlled trials

Abstract: This systematic review showed that ECT appears to be an effective and safe treatment for older adult patients with major depressive disorder. Further high-quality studies with extended follow-up are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…Overall, no serious adverse events were reported during the course of the study. This is consistent with the literature reviews indicating the safety of ECT in elderly patients 5, 11,38–40 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, no serious adverse events were reported during the course of the study. This is consistent with the literature reviews indicating the safety of ECT in elderly patients 5, 11,38–40 …”
Section: Discussionsupporting
confidence: 92%
“…Electroconvulsive therapy (ECT) appears to be much more efficient treatment in elderly patients wherein pharmacotherapy is often poorly tolerated or ineffective. A review of randomised controlled trials comparing ECT and pharmacotherapy in the population of older patients indicated ECT therapy as more effective ‐ the response rates were 80–97% versus 63–73% among patients treated with ECT and pharmacotherapy, respectively 5 . ECT has been proven to be an effective method of treatment even in cases of co‐occurrence of somatic diseases, vascular or neurodegenerative lesions in the brain 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of clinical studies have confirmed that although their curative effect is accurate, it is limited by the slow onset and low efficiency. Compared with the curative effect of drug therapies, electroconvulsive therapy (ECT) for depression has a higher efficiency rate and quicker onset (Dong et al., 2018; Rhebergen et al., 2015), especially after the introduction of anesthetics and muscle relaxants used during the procedure. The modified ECT not only eliminates the patients' fear and reduces the stress response, but also has been widely used worldwide as it reduces the incidence of adverse events, such as fracture, tooth injury, and cardiovascular and cerebrovascular accidents.…”
Section: Introductionmentioning
confidence: 99%